PENGARUH AMBIGUITAS PERAN DAN BEBAN KERJA TERHADAP KINERJA TUGAS DAN KINERJA KONTEKSTUAL KARYAWAN (Studi pada Hotel Kelas Melati di Semarang) - Susanto, Agustin Erawati (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2011)
Competition in hotel business make owner hotels vying to give the best hotel image. Hotel's performance can't be separate from task and contextual performance's employees. Factors that influencing task and contextual performance's employees are role ambiguity and workload. So, the research was conducted to see how influence of role ambiguity and workload to task and contextual performance's employees.This research was conducted at six non star hotels in Semarang with the number of respondent who took part in were 131 employees. The collection of data was using questionnaire techniques. The data analysis technique in this research is SEM or Structural Equation Modeling.Based on the result calculated by AMOS 16, the obtained result that all the hypotheses proposed was acceptable. Role ambiguity had negative impact and significant on employee's task performance, Role ambiguity had negative impact and significant on employee's contextual performance, workload had negative impact and significant on employee's task performance and workload had negative impact and significant on employee's contextual performance. The research had shown that role ambiguity was the largest factor influencing the employee's task and contextual performance. Based on the above findings, the model proposed in this research could be accepted.